Surface dielectric barrier discharge plasma for reducing zearalenone toxicity: comparative efficacy and mechanisms in gas and liquid-phase degradation - Yongqin Fan; Junxia Feng; Xiaoying Zhou; Renwu Zhou; Shuai Zhang; Jiasui Zhan; Zhen Jiao; Ruonan Ma; Tao Shao (Food Research International, 2026)

Dissolved oxygen dynamics in shallow lakes under climate change: Synergistic modulation by nutrient loading - Fan Zhang; Xiaohong Shi; Shengnan Zhao; Ruonan Hao; Shihuan Wang; Ruli Kang; Lauri Arvola (Journal of Hydrology, 2026)

Multiscale hybrid strategy for high-performance flexible pressure sensors with high sensitivity and wide working range - Ruonan Zhang; Naida Ding; Han Wang; Tian-Yu Zhang; Chaoqun Ma; Huijie Fan; Zhi Han; Chang Liu; You Zeng (Chemical Engineering Journal, 2026)

Advances in fungal ergothioneine: from biosynthesis to AI-driven industrial biomanufacturing - Yangyang Wu; Lingxi Fan; Ruonan Xu; Shuangxi Xing; Yujun Sun (Natural Product Research, 2026)

Towards operational safety in maritime transportation: a neurophysiological workload measurement using deep learning - Ruonan Jiang; Shiqi Fan (Ocean Engineering, 2026)

Passive atmospheric wind profile retrieval via multi-region microwave radiometer network - Shuailong Jiang; Yingying Ma; Chengwei Li; Lianfa Lei; Boming Liu; Shikuan Jin; Hui Li; Weiyan Wang; Ruonan Fan; Yujie Wang; Ao Miao; Wei Gong (Atmospheric Research, 2026)

Distribution patterns of potentially toxic elements in rhizosphere and non-rhizosphere soils of dominant plant species in the Yellow River Delta - Siqi Tong; Yuqing Fan; Yali Yang; Yanfeng Shi; Ming Li; Ruonan Wang; Xiaohui Liu; Bin Zhao (Environmental Monitoring and Assessment, 2025)

Stage-specific cadmium tolerance based on morphological and physiological characteristics in marine macroalgae Grateloupia turuturu and Pachymeniopsis lanceolata - Pinhan Li; Chen Zhang; Yuhang Song; Ruonan Wang; Meiqi Sun; Wei Fan; Hongwei Wang; Yao Bian (Algal Research, 2025)

Potential use of plasma-activated water cleaning for aflatoxin B1 degradation in peanuts - Ruonan Ma; Cui Xu; Junxia Feng; Hangbo Xu; Yongqin Fan; Guoyu Zhou; Ximei Dai; Dongjie Cui; Zhen Jiao (Food Chemistry, 2025)

Different atmosphere anneals modulation Au size increasing Au-TiO2 interaction boosting photogenerated carrier separation efficiency to enhance photocatalytic hydrogen evolution - Zheyuan Fan; Yiqiao Wang; Ruonan Hou; Rong Zhong; Yu Xie; Lianjun Liu; Yun Ling (Fuel, 2025)

Influence of clouds on planetary boundary layer height: A comparative study and factors analysis - Hui Li; Boming Liu; Wei Gong; Yingying Ma; Shikuan Jin; Weiyan Wang; Ruonan Fan; Shuailong Jiang (Atmospheric Research, 2025)

Soil moisture drought and diverse impacts on vegetation across the Tibetan Plateau in recent three decades - Yongwei Liu; Xingwang Fan; Wen Wang; Han Zhou; Chengmei Luan; Ruonan Wang; Rong Wang; Yuanbo Liu (Science of The Total Environment, 2025)

Occurrence of Volatile Organic Compounds and Associated Risk Assessments in Dongting Lake, China - Ruonan Wang; Liyuan Yang; Yuqing Fan; Shichao Ma; Siqi Tong; Xiaochun Guo; Shaoyong Lu (Water, Air, & Soil Pollution, 2025)

Growth performance, antioxidant capacity, intestinal microbiota, and metabolomics analysis of Nile tilapia (Oreochromis niloticus) under carbonate alkalinity stress - Qiuran Yu; Fan Zhang; Ruonan Li; Erchao Li; Jianguang Qin; Liqiao Chen; Xiaodan Wang (Aquaculture, 2025)

Magnetic nanoparticle modified moss Biochar: A novel solution for effective removal of enrofloxacin from aquaculture water - Ruonan Yang; Zhonghua Li; Chompoonuch Pitakrattanawong; Lei Zhu; Bingzhi Li; Longxiang Fang; Limin Fan; Chao Song; Shunlong Meng (Journal of Environmental Management, 2025)

Hypoxia cycle in shallow lakes during winter (ice-covered to melting period): Stable and decay, hypoxia, and recovery phases - Fan Zhang; Xiaohong Shi; Shengnan Zhao; Ruonan Hao; Biao Sun; Shuang Song; Guohua Li (Science of The Total Environment, 2024)

New insights into black carbon light absorption enhancement: A comprehensive analysis of two differential behaviors - Ruonan Fan; Yingying Ma; Wenxiang Cao; Shikuan Jin; Boming Liu; Weiyan Wang; Hui Li; Wei Gong (Environmental Pollution, 2024)

The effect of tomato and lycopene on clinical characteristics and molecular markers of UV-induced skin deterioration: A systematic review and meta-analysis of intervention trials - Xiaofeng Zhang; Qilun Zhou; Yue Qi; Xiaoli Chen; Jinlan Deng; Yongping Zhang; Ruonan Li; Jianming Fan (Critical Reviews in Food Science and Nutrition, 2024)

Effect of surface water on wollastonite carbonation: Activated dissolution and mass transfer - Tao Wang; Wenjing Tang; Wei Zhang; Zhenwei Yi; Ruonan Guo; Li Zhang; Kun Luo; WenYang Fan; Xiang Gao (Chemical Engineering Journal, 2024)

Effects of the Glucocorticoid-Mediated Mitochondrial Translocation of Glucocorticoid Receptors on Oxidative Stress and Pyroptosis in BV-2 Microglia - Ruonan Dang; Xuyang Hou; Xinglan Huang; Caifeng Huang; Xiaoqing Zhao; Xingrong Wang; Ning Zhang; Yuqi Yang; Nan Li; Sheng Liu; Peng Yan; Ping Fan; et al. (Journal of Molecular Neuroscience, 2024)

Cortical thickness of the inferior parietal lobule as a potential predictor of relapse in men with alcohol dependence - Kebing Yang; Ruonan Du; Qingyan Yang; Rongjiang Zhao; Fengmei Fan; Song Chen; Xingguang Luo; Shuping Tan; Zhiren Wang; Ting Yu; Baopeng Tian; Thang M. Le; et al. (Brain Imaging and Behavior, 2023)

Metal oxide nanoparticles inhibit nitrogen fixation and rhizosphere colonization by inducing ROS in associative nitrogen-fixing bacteria Pseudomonas stutzeri A1501 - Chao Lu; Ruonan Hei; Xiuchao Song; Zixian Fan; Dejie Guo; Jia Luo; Yan Ma (Chemosphere, 2023)

From anaerobic digestion to single cell protein synthesis: A promising route beyond biogas utilization - Rui Li; XiaoLei Fan; YuFeng Jiang; RuoNan Wang; RongBo Guo; Yifeng Zhang; ShanFei Fu (Water Research, 2023)

Identification of miR-192 target genes in porcine endometrial epithelial cells based on miRNA pull-down - Qingchun Li; Ruonan Gao; Yansen Chen; Su Xie; Xiaomei Sun; Hongbing Gong; Fan He; Yishan Sun; Shihao Lu; Xin Chen; Mengfan Qi; Mingguo Li; et al. (Molecular Biology Reports, 2023)

Validation, analysis, and comparison of MISR V23 aerosol optical depth products with MODIS and AERONET observations - Ruonan Fan; Yingying Ma; Shikuan Jin; Wei Gong; Boming Liu; Weiyan Wang; Hui Li; Yiqun Zhang (Science of The Total Environment, 2023)

Porous Cobalt-nickel phosphides prepared from Al-doped NiCo-LDH precursors for supercapacitor and electrocatalysis applications - Ruonan Liu; Lulu Chen; Fei Mo; Haiyan Song; Guang Yang; Chunxia Chen; Xiaoliang Wu; Yichao Huang; Zhuangjun Fan (Chemical Engineering Journal, 2023)

Fine mapping of powdery mildew and stripe rust resistance genes Pm5V/Yr5V transferred from Dasypyrum villosum into wheat without yield penalty - Ruiqi Zhang; Chuntian Lu; Xiangru Meng; Yali Fan; Jie Du; Runran Liu; Yigao Feng; Liping Xing; Petr Cápal; Kateřina Holušová; Jaroslav Doležel; Yiwei Wang; et al. (Theoretical and Applied Genetics, 2022)

Flavonoids improve drought tolerance of maize seedlings by regulating the homeostasis of reactive oxygen species - Baozhu Li; Ruonan Fan; Guiling Sun; Ting Sun; Yanting Fan; Shenglong Bai; Siyi Guo; Shiquan Huang; Jiong Liu; Hui Zhang; Pengtao Wang; Xiaohong Zhu; et al. (Plant and Soil, 2021)
Background and aims As drought threatens the yield and quality of maize ( Zea mays L.), it is important to dissect the molecular basis of maize drought tolerance. Flavonoids, participate in the scavenging of oxygen free radicals and alleviate stress-induced oxidative damages. This study aims to dissect the function of flavonoids in the improvement of maize drought tolerance. Methods Using far-infrared imaging screening, we previously isolated a drought overly insensitivity ( doi ) mutant from an ethyl methanesulfonate (EMS)-mutagenized maize library and designated it as doi57 . In this study, we performed a physiological characterization and transcriptome profiling of doi57 in comparison to corresponding wild-type B73 under drought stress. Results Under drought stress, doi57 seedlings displayed lower leaf-surface temperature (LST), faster water loss, and better performance in growth than B73. Transcriptome analysis reveals that key genes involved in flavonoid biosynthesis are enriched among differentially expressed genes in doi57 . In line with these results, more flavonols and less hydrogen peroxide (H 2 O 2 ) were accumulated in guard cells of doi57 than in those of B73 with the decrease of soil water content (SWC). Moreover, the capacity determined from doi57 seedling extracts to scavenge oxygen free radicals was more effective than that of B73 under the drought treatment. Additionally, doi57 seedlings had higher photosynthetic rates, stomatal conductance, transpiration rates, and water use efficiency than B73 exposed to drought stress, resulting in high biomass and greater root/shoot ratios in doi57 mutant plants. Conclusion Flavonoids may facilitate maize seedling drought tolerance by lowering drought-induced oxidative damage as well regulating stomatal movement.

FLOURY ENDOSPERM12 Encoding Alanine Aminotransferase 1 Regulates Carbon and Nitrogen Metabolism in Rice - Mingsheng Zhong; Xi Liu; Feng Liu; Yulong Ren; Yunlong Wang; Jianping Zhu; Xuan Teng; Erchao Duan; Fan Wang; Huan Zhang; Mingming Wu; Yuanyuan Hao; et al. (Journal of Plant Biology, 2019)

Far infrared imaging, an effective way to screen maize seedling mutants for drought stress response - Baozhu Li; Ruonan Fan; Shiquan Huang; Lei Peng; Jingxuan Guo; Qidi Zhan; Xiang Zhao; Chunpeng Song (Biologia, 2017)